2019
DOI: 10.5829/ije.2019.32.12c.06
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Energy Absorption Capacity of Glass Reinforced SCC Beams

Abstract: A B S T R A C TVarious experimental studies have been carried out on glass fiber reinforced concrete (GFRC), but in limited studies, the behavior of this type of concrete is evaluated using finite element method (FEM). In this study an analysis model is presented for predicting energy absorption capacity of glass fiber reinforced self-compacting concrete (GFRCSCC) beams and the results are compared with experimental study. For this purpose, the investigations are conducted in two experimental and numerical sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The slump flow diameter of specimens containing 0, 0.25, 0.5, 0.75, 1 and% GF were decreased 0.14, 0.29, 2.4, and 2.7 %. Fibers prevent the flowability of cement paste [38,39]. Güneyisi et al [40] showed that using 1% GF reduces the slump flow diameter by about 6% [40].…”
Section: Fresh Concrete Resultsmentioning
confidence: 99%
“…The slump flow diameter of specimens containing 0, 0.25, 0.5, 0.75, 1 and% GF were decreased 0.14, 0.29, 2.4, and 2.7 %. Fibers prevent the flowability of cement paste [38,39]. Güneyisi et al [40] showed that using 1% GF reduces the slump flow diameter by about 6% [40].…”
Section: Fresh Concrete Resultsmentioning
confidence: 99%
“…The traction-separation response was described by three failure modes: opening (mode I), sliding I (mode II), and sliding II (mode III). Through literature, many experimental and numerical works have been determined the cohesive damage parameters between the FRCM composite and concrete [13][14][15][16][17] and these values will guide the researcher in the future studies. Based on these studies, the CBM parameters including initial elastic stiffness ( 0 ) in kN/mm, maximum shear stress ( ) , and fracture energy ( ) N/mm, are ranged between (1.5-9.85), (0.2-1.5), and (0.24-1.5); respectively.…”
Section: Frcm-concrete Interface Modelmentioning
confidence: 99%
“…Most of the previous studies focused on theoritical and numerical studies of structures strengthened with FRP systems [14][15][16][17]. A numerical finite element analysis of RC beams strengthened with EB-FRP techniques was implemented [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has accelerated the advancements in numerous fields of research, such as fluid mechanics, mechanics of structures, fracture mechanics, heat conduction, and biomechanics. It has been proven that this approach, which is labor-intensive to build, calculate, and analyze models, is successful in resolving problems of design improvements [ 30 , 31 , 32 ]. The Abaqus FEM code has been effectively used in much culvert-related research for design and analysis [ 16 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%